An intermittent detachment faulting system with a large sulfide deposit revealed by multi-scale magnetic surveys - Tao Wu (Nature Portfolio, 2021)
In ultraslow-spreading ridges intermittent detachment faulting could contribute to discontinuous magmatic accretion supporting the development of massive sulfide deposits. Here the authors using a multi-scale magnetic survey of the Southwest Indian Ridge constrain that an episode of detachment faulting took place 0.7-1.48 Ma, with the present fault active since 0.33 Ma.